2011
DOI: 10.1182/blood.v118.21.5198.5198
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Obesity and Lymphoma: A Meta-Analysis of Prospective Cohort Studies

Abstract: 5198 Introduction: Lymphoma is a common hematologic malignancy, etiology of which remains largely unclear. Obesity and overweight have been associated with an increased risk of developing lymphoma; however, with conflicting results. The main objective of this meta-analysis is to evaluate the potential relationship that overweight and obesity may have in the development of lymphoma in adults. A secondary objective was to evaluate the risk of separate lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We analyzed previously reported genetic associations of the selected IVs with known lymphoma confounding factors, such as obesity-related traits [ 41 , 42 ] or smoking [ 43 , 44 ] ( Supplementary Table S3 ). Only the variant rs653178 showed evidence of association with possible confounding factors for lymphoma ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed previously reported genetic associations of the selected IVs with known lymphoma confounding factors, such as obesity-related traits [ 41 , 42 ] or smoking [ 43 , 44 ] ( Supplementary Table S3 ). Only the variant rs653178 showed evidence of association with possible confounding factors for lymphoma ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the significant models were validated after removing SNPs associated with known lymphoma confounding factors such as obesity [ 41 , 42 ], and tobacco smoking [ 43 , 44 ] ( Supplementary Table S3 ), as reported by the PhenoScanner v2 [ 84 ].…”
Section: Methodsmentioning
confidence: 99%
“…Probably, this may be caused not only because HL and NHL are heterogenous diseases that involve many histological subtypes but also due to other variables such as location, gender, or age, as previously explained. In line with this notion, Willet et al (2008) concluded that there was no evidence to support obesity as a determinant parameter for all types of NHL combined, whereas Ingham et al (2011) found that obesity was associated with the risk of HL and most types of NHL, excluding FL [ 51 ].…”
Section: Obesity and Lymphomamentioning
confidence: 99%
“…As per international cancer data trends, the incidence of lymphoma has been continuously rising ( 4 , 5 ). The cause of lymphoma is not entirely clear, although previous studies have suggested a possible link to factors such as smoking ( 6 ), alcohol consumption ( 7 ), obesity ( 8 ), viral infections ( 9 , 10 ), ionizing radiation exposure ( 11 ), chemical exposure ( 12 ), autoimmune diseases, or immune dysfunction ( 13 ). Moreover, there is mounting evidence that the gut microbiota significantly affect lymphoma pathogenesis, treatment response, and prognosis ( 14 ).…”
Section: Introductionmentioning
confidence: 99%